HUBUNGAN ANTARA STRES KERJA DENGAN PERILAKU CARING PERAWAT DI RUANG RAWAT INAP MAYAPADA HOSPITAL TANGERANG - Rini Setyowati; Retno Andriati; Ayu Rahayu; Marsondang Situmeang; Dyna Meilolita; Dwi Septianingsih (CV. Denasya Smart Publisher, 2025)
Nurses have an important role in implementing caring in the provision of nursing care. Nurses’ workload has a significant influence on high stress levels and on the implementation of caring behaviors. A preliminary study conducted in the inpatient ward of Mayapada Hospital Tangerang showed that three out of five nurses experienced a moderate level of stress. This study aimed to identify the relationship between stress levels and nurses’ caring behavior at Mayapada Hospital Tangerang. The research method used in this study was a descriptive correlational design. The population consisted of nurses working in the inpatient wards of Building 3 at Mayapada Hospital Tangerang, with a total sample of 32 respondents selected using a total sampling technique. Data were collected using the Expanded Nursing Stress Scale (ENSS) questionnaire and the Caring Behavior Inventory (CBI-24) questionnaire. Data analysis included univariate analysis, which was presented in the form of frequency distributions, and bivariate analysis using the Chi-Square test. The results showed that most nurses with high levels of work-related stress had low caring behavior, totaling 15 respondents (75%). Meanwhile, almost all nurses with low stress levels demonstrated high caring behavior, with 10 respondents (83.3%). Based on the Chi-Square test results, a p-value of 0.005 was obtained (p-value < α 0.05), indicating a significant relationship between work-related stress and nurses’ caring behavior in the inpatient wards of Mayapada Hospital Tangerang. In conclusion, a relationship was found between nurses’ work stress levels and caring behavior. Therefore, various efforts are needed to improve the quality of nursing care services based on caring principles through the implementation of effective and well-directed management, as well as programs such as training and workshops on stress management for nurses.